KAJIAN EKOLINGUISTIK METAFORIS PADA UPACARA ADAT PERNIKAHAN DI KECAMATAN BANTARKAWUNG: Array - Yani, Tri Andra; Irma, Cintya Nurika (Universitas Peradaban, 2022)
This study aims to analysis, describe, and identification form ecolinguostics metaphor from the traditional wedding ceremony in districts Bantarkawung. The research method used in this research is qualitativ descriptive. This research is provided through the listen and note method with recording techniques, interview, and continued with documentation. The result of this research shows that is a narrative form metaphor in the traditional wedding procession in thr Pngarasan, Kebandungan, and Ciomas village. The form metaphor that appears is lexical where metaphor form are found in narrativ that contain meaning in relation to the natural environment a speech community. The language used in the procession traditional wedding ceremony is expressed in meaning through symbol which include various form of conditions theat must be fulfilled in the procession traditional wedding ceremony,as the ecological forms of human, plants, animal, and crops. Forms merriage customs and traditions that are communicated through verbal and nonverbal symbol show lexical meaning classified in the form of noun with nouns, noun with verb, noun with adjektive, and verb with adjektive.